Penguatan Desa Proiklim Melalui Zero Waste dan Ketahanan Pangan di Desa Karang Buah Kabupaten Barito Kuala - Nabila, Siti; An'Amta, Dimas Asto Aji; Rahmah, ST.; Rahul, Muhammad; Ruswati, Anis; Noor, Hakiki; Ru'yah, Rabiatul; Akbar, Muhammad Hadi (Prodi Sosiologi FISIP ULM, 2024)
In 2022 Karang Buah Village was appointed by Barito Kuala Regency to become a Proiklim Lestari Village, but to raise the status to become a Climate Village must pass through many stages, one of which is the problem of waste. Although the community has an awareness not to throw garbage in the river, the absence of TPS and waste bank means that people often burn garbage as a final solution for waste disposal. This is a challenge to implement Desa Iklim, as it contradicts the Proiklim principle. The solution in the form of a program is present not only to overcome waste management problems, but also to strengthen the Proiklim Village. The waste decomposition period education sign program was created to educate the community, the sign was then placed in front of the village office. The eco enzyme socialization and training program, as well as the ecobrick garden were made to provide solutions in managing waste, for the eco enzyme program in collaboration with Eco Enzyme Nusantara South Kalimantan and carried out at the village hall, while the ecobrick garden program was made using waste obtained from mutual cooperation and the results were placed at SDN Karang Buah. The hydroponic cultivation program was created to strengthen food security by providing another solution in cultivating plants, the cultivation pilot was placed at the village office. Finally, a storytelling program with the theme of protecting the environment was created as an early education to protect the environment, this program was implemented at SDN Karang Buah. The successful achievement of the programs that have been implemented can be seen from the survey given to the community. The results showed that more than 90% of the community agreed that the program provides long-term benefits for the community and village.